2022
DOI: 10.3390/jcm11092586
|View full text |Cite
|
Sign up to set email alerts
|

The Upshot of the SARS-CoV-2 Pandemic on Nursing Assistants: Evaluating Mental Health Indicators in Huelva

Abstract: Healthcare professionals who work in front-line situations are among those under the highest risk of presenting negative mental health indicators. We sought to assess the prevalence of low personal realization, emotional exhaustion, and depersonalization as well as probable non-psychotic psychiatric pathologies during the pandemic in nursing assistants in the city of Huelva (Spain), and to study the association between these mental health indicators and sociodemographic and professional variables. A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The mental health of nurses should be an object of improvement for all health authorities, and many authors confirm this [ 38 ]. An increase in burnout among workers leads to worsening of the care they give to users.…”
Section: Discussionmentioning
confidence: 99%
“…The mental health of nurses should be an object of improvement for all health authorities, and many authors confirm this [ 38 ]. An increase in burnout among workers leads to worsening of the care they give to users.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found significative gender differences related to emotional exhaustion and depersonalization that were more prevalent in men than in women. These data underline that gender differences must be taken into account when implementing public health measures to defend the neuropsychological well-being of workers in high-risk categories [ 8 ].…”
mentioning
confidence: 99%